MCT1 lactate transporter blockade re-invigorates anti-tumor immunity through metabolic rewiring of dendritic cells in melanoma - Camille Niveau; Mélanie Cettour-Cave; Stéphane Mouret; Eleonora Sosa Cuevas; Mylene Pezet; Benoît Roubinet; Hugo Gil; Florence De Fraipont; Ludovic Landemarre; Julie Charles; Philippe Saas; Caroline Aspord (Nature Communications)
Abstract Dendritic cells (DC) are key players in antitumor immune responses. Tumors exploit their plasticity to escape immune control; their aberrant surface carbohydrate patterns (e.g., glycans) shape immune responses through lectin binding, and manipulate the metabolism of immune cells, including DCs to alter their function and escape immune surveillance. DC metabolic reprogramming could induce immune subversion and tumor immune escape. Here we explore metabolic features of human DC subsets (cDC2s, cDC1s, pDCs) in melanoma, at single cell level, using the flow cytometry-based SCENITH (Single-Cell ENergetIc metabolism by profiling Translation inHibition) method. We demonstrate that circulating and tumor-infiltrating DC subsets from melanoma patients are characterized by altered metabolism, which is linked to their activation status and profile of immune checkpoint expression. This altered metabolism influences their function and affects patient clinical outcome. Notably, melanoma tumor cells directly remodel the metabolic profile of DC subsets, in a glycan-dependent manner. Strikingly, modulation of the mTOR/AMPK-dependent metabolic pathways and/or the MCT1 lactate transporter rescue cDC2s and cDC1s from skewing by tumor-derived glycans, Sialyl-Tn antigen and Fucose, and restore anti-tumor T-cell fitness. Our findings thus open the way for appropriate tuning of metabolic pathways to rescue DCs from tumor hijacking and restore potent antitumor responses.